The Role of Smart Medical Equipment and AI in Enhancing Radiology, Dentistry, and Nutrition-Related Health Information Systems - Hakami, Laila Hamad; Al-Haisi, Ibrahim Hamad Manea; Ali Al-Jaafar, Ahmed Jassim; Alamir, Mona Abbas Mousa; Almutairi, Mohammed Khashman; Albalawi, Ohuad Mubark; Almutairi, Saleh Jameel; Aloraini, Raghad Shaya Ali; Asiri, Shareefah Mousa; Alenezi, Khaled Abdulhadi; Haqwi, Mohammed Ahmed Ali (Journal of Ecohumanism, 2024)
The integration of smart medical equipment and artificial intelligence (AI) into healthcare systems has significantly improved diagnostics, treatment planning, and patient outcomes. AI-driven technologies are increasingly employed in radiology, dentistry, and nutrition-related health information systems to optimize efficiency, accuracy, and personalized care. These technological advancements enhance the performance of various healthcare professionals, including radiologists, health information technicians, nutritionists, food and nutrition specialists, family dentists, dental assistants, and medical equipment professionals. AI enhances imaging precision in radiology by detecting abnormalities in X-rays, CT scans, and MRIs with greater accuracy than traditional methods. In dentistry, AI-powered diagnostic tools and automated treatment plans improve the efficiency and precision of procedures, leading to enhanced patient outcomes. In nutrition and dietetics, AI-based platforms analyze dietary habits, health data, and metabolic patterns to create personalized nutrition plans, aiding in chronic disease management and preventive care. Smart medical equipment, such as AI-assisted imaging devices, robotic-assisted surgical tools, automated laboratory analyzers, and wearable health monitors, is revolutionizing healthcare by enabling real-time patient monitoring and early disease detection. These innovations contribute to faster diagnosis, reduced human error, and more efficient treatment planning. Despite its advantages, AI and smart medical equipment present challenges, including data security concerns, high implementation costs, and the need for continuous professional training. This review explores the transformative role of AI in healthcare, its impact on different specialties, and its future potential in shaping modern medical practices.